Activities of local governments for citizen power using the example of the city of Słupsk - Błażejowska, Małgorzata (Działania organów samorządowych na rzecz energetyki obywatelskiej na przykładzie miasta Słupsk, 2019)
The aim of the article is to present the initiatives and activities of local governments to support citizen power, using the example of the Municipal Office in Słupsk. Thanks to intersectoral cooperation, the inhabitants had the opportunity to take advantage of the free replacement of LED lighting and thermostats from Danfoss, which resulted in 20% savings and the reduced energy poverty. Greenpeace funded a photovoltaic installation for a school and IKEA for a homeless shelter. As part of the SCORE program, the city implemented a pilot solution of consumer shareholding, so that the benefits of renewable energy can be accessed by the citizens. An important role in this process is also played by the Bioenergetic Cluster initiated by the local government. Słupsk was the first city in Poland to set up a presidential council and plenipotentiary for sustainable development and the green modernization of the city, green points and introduced integrated ecological education
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 7-15
Keywords: community power; local government; intersectoral cooperation; ecological education; energetyka obywatelska; organy samorządowe; międzysektorowa współpraca; edukacja ekologiczna